The place and role of the methonymic image in the formation of the medieval phraseology fund (on the basis of the “Dictionary of the Russian language of the 11th-17th centuries”) (Eurasian Journal of Philology Science and Education, 2021)
The article is dedicated to the problem connected with the study of the specifics of the semanticstructure of phraseological units of the Great Russian nationality epoch. The aim of the this work is toclarify the ways of establishing, developing and further formation of phraseology fund of the MiddleAges, and the Russian phraseology fund as a whole is formed. On the basis of the analysis of the idiom’sinternal form, the units constructed on methonymic transfer are selected for the study by idiom. Theclassification of the language material has made it possible to identify several types of methonymictransfer, which are actively involved in the formation of the medieval Russian phraseology. For each typeof methonymic transfer examples of language units from different spheres of operation are given. Theanalysis of the language material took into account the specifics of the medieval book culture, in particularthe sphere of the use of phraseological units (religious, legal and military spheres). In this article thefollowing methods and techniques of studying and descriptions of the idioms had been used: descriptivemethod with some elements of component analysis; the technique of complete sampling of the facts;classification; the technique of statistics. As a result, the study highlighted the most productive types ofmethonymic image underlying the formation of sustainable units. The study made it possible to clarifythe ways in which the phraseological fund of the Middle Ages was formed. The study evaluates this periodas one of the important stages, which determined